Analytical model of LDMOS with a single step buried oxide layer. (September 2016) - Yuan, Song; Duan, Baoxing; Cao, Zhen; Guo, Haijun; Yang, Yintang
Abstract: In this paper, a two-dimensional analytical model is established for the Single-Step Buried Oxide SOI structure proposed by the authors. Based on the two-dimensional Poisson equation, the analytic expression of the surface electric field and potential distributions for the device is achieved. In the SBOSOI (Single-Step Buried Oxide Silicon On Insulator) structure, the buried oxide layer thickness changes stepwise along the drift region, and the electric field in the oxide layer also varies with the different buried oxide layer thickness. These variations will modulate the surface electric field distribution through the electric field modulation effects, which makes the surface electric field distribution more uniform. As a result, the breakdown voltage of the device is improved by 60% compared with the conventional SOI structure. To verify the accuracy of the analytical model, the device simulation software ISE TCAD is utilized, the analytical values are in good agreement with the simulation results by the simulation software. The results verified the established two-dimensional analytical model for SBOSOI structure is valid, and it also illustrates the breakdown voltage enhancement by the electric field modulation effect sufficiently. The established analytical models will provide the physical and mathematical basis for further analysis of the new power devices with the patterned buried oxide layer. Highlights: The analytic model for the SBOSOI (Single-Step Buried Oxide Silicon On Insulator) structure is achieved. The breakdown voltage enhancement of the SBOSOI with about 60% higher than conventional SOI LDMOS is observed. The electric field modulation effect is explained through the analytical model. The fully depletion criterion and RESURF criterion for the SBOSOI structure is achieved. The different breakdown conditions at the junctions in the device are analyzed.